Clinical Characteristics of Ocular Toxoplasmosis Patients - Frashad Fanseca Alvarez; Petty Purwanita; Indri Seta Septadina (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Toxoplasma gondii infection causes posterior uveitis and blindness. The diagnosis of ocular toxoplasmosis is based on typical clinical findings accompanied by positive anti-Toxoplasma serology. This study aims to see the clinical characteristics of ocular toxoplasmosis patients. Cross-sectional observational descriptive research is done. This study used 2019-2021 medical records from RSUP Dr. Mohammad Hoesin Palembang patients. The highest incidence of ocular toxoplasmosis at RSUP Dr. Mohammad Hoesin Palembang in 2019-2021 occurred in 2021 (54.5%). The most common age range found in this case is the age group of 0-19 years (45.5%) and the majority are women (72.7%). The majority of patients are out of work (45.5%) and live outside Palembang (81.8%). The most lateralization was found in the right eye (63.6%). The most commonly complained clinical symptom is blurred vision (90.9%). Clinical signs were found lesions of retinochoroiditis in the macular (45,5%), in the extramacular (18,2%), chorioretinal scar (90,9%), vitritis (54,5%), decreased visual acuity (100%), and increased IOP (36,4%). Anti-Toxoplasma IgG was found positive in all patients. The highest incidence of ocular toxoplasmosis was found in 2021. The most commonly complained clinical symptom is blurred vision and the most commonly found clinical sign is a decrease in visual acuity.